2010
DOI: 10.1152/jn.00590.2010
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Noise Sources Shape Patterns of Arm Movement Variability in Three-Dimensional Space

Abstract: Reaching movements are subject to noise in both the planning and execution phases of movement production. The interaction of these noise sources during natural movements is not well understood, despite its importance for understanding movement variability in neurologically intact and impaired individuals. Here we examined the interaction of planning and execution related noise during the production of unconstrained reaching movements. Subjects performed sequences of two movements to targets arranged in three v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 41 publications
9
31
0
Order By: Relevance
“…The fact that the clockwise and counterclockwise sequences typically had their largest components of movement variability along the depth axis might seem surprising as by design these sequences did not require significant movement components in depth. However, this observation is consistent with the findings of Apker et al (2010), which were obtained under similar conditions. Moreover, these investigators showed that this trend was not related to the orientation of the terminal components of the average, executed movements in the frontal plane, which were largely orthogonal to the depth axis in that study and the present one (see Fig.…”
Section: Variable Errors With Visual Feedbacksupporting
confidence: 93%
See 4 more Smart Citations
“…The fact that the clockwise and counterclockwise sequences typically had their largest components of movement variability along the depth axis might seem surprising as by design these sequences did not require significant movement components in depth. However, this observation is consistent with the findings of Apker et al (2010), which were obtained under similar conditions. Moreover, these investigators showed that this trend was not related to the orientation of the terminal components of the average, executed movements in the frontal plane, which were largely orthogonal to the depth axis in that study and the present one (see Fig.…”
Section: Variable Errors With Visual Feedbacksupporting
confidence: 93%
“…As with the single subject shown in Fig. 3, the average proportion of variance accounted for by the first eigenvector was generally large and very consistent across subjects and sequence types (mean: 77 Ϯ 4%), consistent with other studies of endpoint variability in 3-D space (Apker et al 2010;McIntyre et al 1997McIntyre et al , 1998. In contrast to the single subject data, there was little difference between the average amount of variance accounted for by the eigenvectors for the clockwise/counterclockwise sequences and the eigenvectors for the inward/outward sequences (78 and 76%, respectively).…”
Section: Variable Errors With Visual Feedbacksupporting
confidence: 89%
See 3 more Smart Citations